Reabilitação pulmonar de baixo custo no sistema público de saúde de dois municípios brasileiros: avaliação do preparo dos profissionais e principais barreiras durante a sua implementação - Isabella Diniz Faria (2023)
Pulmonary rehabilitation(PR) is an intervention for individuals with chronic respiratory disease(CRD) and brings benefits such as reducing the risk of death, the number of hospitalizations and exacerbations, and consequently the cost of these diseases for the Unified Health System(SUS). Barriers to creating PR programs include the lack of financial resources, difficulties in accessing programs and the lack of training of health professionals. Given this scenario and taking into account the need to expand the offer of PR for individuals with CRD, it is considered essential to promote public policies that enable the implementation of locally adapted and sustainable PR models in Brazil. This thesis aimed to promote the use of low-cost PR(LCPR) as a treatment tool for individuals with CRD, based on a training and technical advisory program for SUS health professionals in two municipalities in Minas Gerais, called Projeto Respirar– Pulmões pela vida – Respire e movimente-se (PRORESP). This thesis gave rise to three studies: 1) survey study, in which a self-administered questionnaire was used that assessed the knowledge, training, confidence and clinical experience of physiotherapists (PT) and the multidisciplinary team (MT), previously applied to a workshop on PR. Forty-four PT and 231 MT professionals participated in the study. This study showed that both PT and MT have low preparation to perform PR, reinforcing the need for continuing education. 2)quasi-experimental study with mixed methods analysis that evaluated the impact of a workshop in LCPR on the knowledge, level of training, clinical experience, confidence and skills of PTs before and after 3 and 12 months of its completion. Of the 44 PT evaluated at the beginning of the study, 34 remained at three months and 22 at 12 months of follow-up. Physiotherapists increased their knowledge about LCPR after three (p = 0.001) and 12 months (p <0.001) of the workshop. The study concluded that training/qualification in LCPR allowed PTs to acquire knowledge and skills for the rehabilitation of individuals with CRD and these gains were maintained for up to 12 months. 3) quasi-experimental study that evaluated the impact of training aimed at the PT team on a pulmonary rehabilitation program with minimal equipment (PRPME) and its results in individuals with CRD. A questionnaire was applied before and another after the PT training, the first to assess expectations regarding the implementation of PR and the second to assess the barriers encountered in creating a PRPME. The six-minute walk test (6MWT) was used to measure the results of the PRPME applied to patients in the 12-month follow-up. Two hundred and seventy five MT professionals participated in the study, of which 44 were PT, in addition to 41 patients with CRD. In conclusion, the study showed that PT training allowed the opening of two PRPMEs and brought benefits to individuals with CRD, with a significant improvement in the 6MWT (p=0.011). The main barriers found were the team's attitudes and their lack of knowledge/training.